CFD on marine propellers - Tong, Chang Yi (2016)
Marine propellers are the most common form of propulsion for ships. Different forms of propellers that are widely used are the standard screw propellers and the ducted propellers. There are numerous experiments and studies to understand its propulsion and compare its performances. Due to the vast differences in geometries, it is difficult to analyze between two propellers. However, investigations are made easier with the existence of modelling software such as Computational Fluid Dynamics (CFD). These software are a versatile tool which benefits the study of marine propellers. The purpose of this report provides a good understanding of the geometry creation of marine propellers using Solidworks, the computational setup and the boundary conditions of the flow parameters using ANSYS Fluent. These setups serve as a guideline to address the complicated simulations that is used to analyze the flow around the propeller and provide a strong foundation for further analysis on other ship components in the future. In this report, two marine propellers, un-ducted and ducted propellers with similar geometry is created. The propellers undergo various experimental conditions using various advance ratios. The results obtained will then be compared and validated with experimental results taken from past references. The CFD simulations show that there are clear distinctions in the open water characteristics when the fluent undergoes different advance velocities. Similarly, there are also differences in the flow and pressure distributions when the fluent flows through different propellers. Finally, conclusions are drawn with recommendations for future work.